Scale solar system: A strategy for teaching sciences and mathematics (Research, Society and Development, 2021)
The National Common Curricular Base points to the development of the theme of astronomy gradually and throughout the stages of basic education, deepening theoretical aspects that reiterate the possibilities of an interdisciplinary approach to Astronomy and its relevance to promote contextualized and meaningful learning. This work describes a didactic sequence entitled “Solar System on a scale” that was developed in a 9th grade class, from an elementary school in the state public network of Uruguaiana / RS, in the first semester of 2020. Seeking to overcome the challenges demanded through remote education, the proposal integrated the areas of Mathematics and Natural Sciences, and was structured in the face of seven meetings, four synchronous and three asynchronous. The students had to perform calculations and represent on a sheet of paper the distances from the planets to the sun, as well as the rays of the planets. The practice allowed to build notions of proportionality in the measures of distance from the planets to the Sun and size of the planets, constituting a great strategy in moments of remote teaching.